ANALISIS CURAHAN WAKTU KERJA DAN HUBUNGANNYA DENGAN PENDAPATAN WANITA PEDAGANG PENGECER SAYURAN (Studi Kasus Di Kota Bengkulu) - Nurung, M.; Priyono, Basuki Sigit; Yuniarti, Fera (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2007)
The research aim to know analize of working time and related wich the woman’s vegetable’s retailer income (case in market of Bengkulu city) the research executed on July’s 27 – Agus’t 27 2005.The objek of this research were to know: 1. The reason why the women work as vegetable's retailer, 2.The factors that related with women's working time, 3. The related between working time witht income of women as vegetable's retailer, 4. Their contribution with household income. The location of this research determined with census method in Pasar Minggu, Pasar Baru Koto I, pasar Panorama, Pasar Pagar Dewa. The responden in this research determined with census method with respondent of 28 persons.The information, that used in this research, based on primary and secondary data. The analysis that used are deskriptive method, income analyze, Rang Spearman Corelation by using two tail of t test whit confidence level of 95% ( = 0.025) and contribution analyze. The result of the research showed that the reason why working as vegetable' retailerbecause economic, social and culture motive. Related to working time the motivation and perception are factor relatec to working time. The result of analyses show that, the average of income was Rp 1.950.937,50 / month and the average of income's contribution was 66,76 %. Key words : working time, vegetable’s retailer income